REINFORCING LEARNING MODEL BASED ISLAMIC BOARDING SCHOOL (PESANTREN) GENERATING GRADUATES EMPOWERED INDONESIA QUONTIENT (InQ) - Chalim, Abdul; Prahesti, Vivin Devi (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Students as santri are more likely to find direction for their goal in learning processes, so learning model based Islamic boarding school (pesantren) give guidance to generate graduates empowered Indonesia Quotient (InQ). The study aims to depict learning model based Islamic boarding school (pesantren) give guidance to generate graduates empowered Indonesia Quotient (InQ).  The study used qualitative research wuth study case. The research was conducted in Islamic Boarding School Api Al Huda with 725 students (santri). The data were collected by using interview, observation and documentation. The interview processes was conducted through teacher who teach in Islamic Boarding School one. The data analysed by Miles and Huberman techniques in which the ones reduced based on the research. The research results that learning model uses simple method that can give an effect on graduates who have Indonesia Quotient (InQ) based on Islamic Boarding School model. The finding study shows Indonesia Quotient (InQ) found in Islamic Boarding School (pesantren) has 4 points such as faith in God Almighty, mutual cooperation, creativity and independent, being implemented in Pesantren